2008
DOI: 10.1007/s10071-007-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of human pointing gestures in young human-reared wolves (Canis lupus) and dogs (Canis familiaris)

Abstract: Dogs have a remarkable skill to use humangiven cues in object-choice tasks, but little is known to what extent their closest wild-living relative, the wolf can achieve this performance. In Study 1, we compared wolf and dog pups hand-reared individually and pet dogs of the same age in their readiness to form eye-contact with a human experimenter in an object-choice task and to follow her pointing gesture. The results showed that dogs already at 4 months of age use momentary distal pointing to Wnd hidden food ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
192
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(204 citation statements)
references
References 37 publications
6
192
0
6
Order By: Relevance
“…Udell et al (2008) examined the use of a pointing cue by five experimental groups of canids (one group of wolves, four groups of dogs), each with eight subjects of adult age. Unlike and Viranyi et al (2008), none of the subjects were reared for the purposes of the experiment, so the authors could not be sure of the subjects' previous relevant experiences. This raises the question of how much previous experience the wolves had with performing human-directed tasks; this is particularly important given that these wolves had been used in public education shows and had been intensively exposed to humans.…”
Section: Reanalysis Of Udell Et Al (2008): Are Wolves More Skilled Tmentioning
confidence: 99%
See 3 more Smart Citations
“…Udell et al (2008) examined the use of a pointing cue by five experimental groups of canids (one group of wolves, four groups of dogs), each with eight subjects of adult age. Unlike and Viranyi et al (2008), none of the subjects were reared for the purposes of the experiment, so the authors could not be sure of the subjects' previous relevant experiences. This raises the question of how much previous experience the wolves had with performing human-directed tasks; this is particularly important given that these wolves had been used in public education shows and had been intensively exposed to humans.…”
Section: Reanalysis Of Udell Et Al (2008): Are Wolves More Skilled Tmentioning
confidence: 99%
“…This conclusion holds even for wolves reared in identical conditions with a group of dogs for the purpose of comparing their social skills with humans. In summary, it is unlikely that dogs simply inherited their unusual skills from their last common ancestor with wolves (Viranyi et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have already revealed some crucial differences in the human related social behaviours of the two species. For example, compared to wolf pups, dog puppies' more intense social interest towards humans is accompanied by relatively greater sensitivity to human behavioural cues (Miklósi et al, 2003;Virányi et al, 2008) and less aggression during non-competitive inter-specific interactions 2009). Moreover, in contrast to dogs, wolves do not show human analogue attachment behaviour to their owners .…”
Section: Introductionmentioning
confidence: 99%